The Einstein effect provides global evidence for scientific source credibility effects and the influence of religiosity - Hoogeveen, Suzanne (2023)
People tend to evaluate information from reliable sources more favourably, but it is unclear exactly how perceivers' worldviews interact with this source credibility effect. In a large and diverse cross-cultural sample (N = 10,195 from 24 countries), we presented participants with obscure, meaningless statements attributed to either a spiritual guru or a scientist. We found a robust global source credibility effect for scientific authorities, which we dub 'the Einstein effect': across all 24 countries and all levels of religiosity, scientists held greater authority than spiritual gurus. In addition, individual religiosity predicted a weaker relative preference for the statement from the scientist compared with the spiritual guru, and was more strongly associated with credibility judgements for the guru than the scientist. Independent data on explicit trust ratings across 143 countries mirrored our experimental findings. These findings suggest that irrespective of one's religious worldview, across cultures science is a powerful and universal heuristic that signals the reliability of information.